Association Between Delayed Graft Function and Graft Loss in Donation After Cardiac Death Kidney Transplants—A Paired Kidney Registry Analysis. Issue 6 (June 2017) - Lim, Wai H.; McDonald, Stephen P.; Russ, Graeme R.; Chapman, Jeremy R.; Ma, Maggie KM.; Pleass, Henry; Jaques, Bryon; Wong, Germaine
Abstract : Background: Delayed graft function (DGF) is an established complication after donation after cardiac death (DCD) kidney transplants, but the impact of DGF on graft outcomes is uncertain. To minimize donor variability and bias, a paired donor kidney analysis was undertaken where 1 kidney developed DGF and the other did not develop DGF using data from the Australia and New Zealand Dialysis and Transplant Registry. Methods: Using paired DCD kidney data from the Australia and New Zealand Dialysis and Transplant Registry, we examined the association between DGF, graft and patient outcomes between 1994 and 2012 using adjusted Cox regression models. Results: Of the 74 pairs of DCD kidneys followed for a median of 1.9 years (408 person-years), a greater proportion of recipients with DGF had experienced overall graft loss and death-censored graft loss at 3 years compared with those without DGF (14% vs 4%, P = 0.04 and 11% vs 0%, P < 0.01, respectively). Compared with recipients without DGF, the adjusted hazard ratio for overall graft loss at 3 years for recipients with DGF was 4.31 (95% confidence interval [95% CI], 1.13-16.44). The adjusted hazard ratio for acute rejection and all-cause mortality at 3 years in recipients who have experienced DGF were 0.98 (95% CI, 0.96-1.01) and 1.70 (95% CI, 0.36-7.93), respectively, compared with recipients without DGF. Conclusions: Recipients of DCD kidneys with DGF experienced a higher incidence of overall and death-censored graft loss compared with those without DGF. Strategies aim to reduce the risk of DGF could potentially improve graft survival in DCD kidney transplants. Abstract : Using the Australia and New Zealand Dialysis and Transplantation Registry together with paired DCD kidney data (1 recipient with DGF and 1 without from the same DCD donor), the authors examine the impact of DGF on long-term graft survival. Overall graft loss and death-censored graft loss are worse in case of DGF suggesting potential graft survival room for improvement in decreasing DGF in this setting.